Insurance, Credit, And Technology Adoption : Field Experimental Evidence From Malawi - Giné, Xavier (The World Bank, 2007)
The adoption of new agricultural technologies may be discouraged because of their inherent riskiness. This study implemented a randomized field experiment to ask whether the provision of insurance against a major source of production risk induces farmers to take out loans to invest in a new crop variety. The study sample was composed of roughly 800 maize and groundnut farmers in Malawi, where by far the dominant source of production risk is the level of rainfall. We randomly selected half of the farmers to be offered credit to purchase high-yielding hybrid maize and improved groundnut seeds for planting in the November 2006 crop season. The other half of the farmers were offered a similar credit package but were also required to purchase (at actuarially fair rates) a weather insurance policy that partially or fully forgave the loan in the event of poor rainfall. Surprisingly, take up was lower by 13 percentage points among farmers offered insurance with the loan. Take-up was 33.0 percent for farmers who were offered the uninsured loan. There is suggestive evidence that the reduced take-up of the insured loan was due to the high cognitive cost of evaluating the insurance: insured loan take-up was positively correlated with farmer education levels. By contrast, the take-up of the uninsured loan was uncorrelated with farmer education